Analisis Sistem Pengelolaan Limbah Medis Padat pada Puskesmas Onembute Kecamatan Onembute Kabupaten Konawe - Ardianto, Ardianto; Rosdiana, Rosdiana; Ndibale, Wa (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2021)
The community health center is one of the health service units which in its activities produces solid medical waste. The Oneembute Health Center, Onembute District, Konawe Regency - Southeast Sulawesi does not yet have an incinerator to manage solid medical waste. In this study, we analyze the solid medical waste management system at the Oneembute Health Center whether it was in accordance with the Regulation of the Minister of Environment and Forestry No.P.56/Menlhk-Setjen/2015 regarding procedures and technical requirements for the management of hazardous waste and hazardous materials. toxic from health care facilities. The research method was applied by using the descriptive research method and qualitative approach. Based on these results showed that the implementation of the solid medical waste management system starting from the sorting stage to the final processing stage of the Onembute Health Center had not fully complied with the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number: P.56/Menlhk-Setjen/2015 concerning Procedures and Requirements. Hazardous Waste Management Techniques from Health Service Facilities.